Politics of Ecology On Environmental Management In Regional Autonomy Perspective In Banjar Regency - Samahuddin Muharram; Fadly Fadly; Dhena Aldhaliaa; Rosa Pebriandini; Falehah Nabila (Wadah Inovasi Indonesia, 2021)
Studies on political ecology problems always start from justice, poverty, resource inequality, population spikes, and environmental damage. This condition tends to only analyze from the side of causality. This causality explanation has a weakness in answering what allows this condition to occur. The problems in these areas are pretty interesting to study further because regional autonomy is a practice. The Provincial Government and Regency Governments play an essential role in the management and regulation of environmental policies. The purpose of this study is to analyze the political ecology related to the interaction between policy (regulation) and environmental management on social and economic conditions from the perspective of regional autonomy. This study uses a descriptive qualitative research approach. This study's data collection techniques are observation (observation), in-depth interviews, and literature study. The types of data in this study include ecological, economic, and social components of environmental ecosystems. The primary assumption in political ecology is that environmental change is not neutral. Instead, it is a form of a politicalized environment that involves many interested actors. Ecology-politics can be interpreted as a political study that understands human relations with environmental changes resulting from political processes. The political ecology perspective emphasizes that internal problems in the environment rather than external influences, namely due to political and economic pressures outside of itself, including the policy of regional autonomy (decentralization) of natural resources, is not just a technical problem. There are socio-political problems related to access to use and control over natural resources (power and authority). Environmental management problems are caused primarily not by technical failures but also by political failures. This means that the approach in environmental management is sectoral, technocratic, exclusive, and elitist, without considering the economic, social, and political forces that are the leading causes of the destruction of natural resources.